Combining biotechnology with sustainability: feasibility of bioenergy sorghum in generating high-value bioproducts - Trine B. Andersen; Elliot Braun; Brianna N. I. Brown; Bjoern Hamberger; Leah Knoor; İlayda Korkmaz; Lucas Reist; Luke Sharpe; Brian Adam McKinley; James O. Suggitt; Mitchell A. Ticoras; Angel Indibi (Biotechnology Letters, 2025)
Biofuels generated through fermentation of plant-derived lignocellulosic biomass are currently not competitive with fossil fuels. Here, a framework is described for the engineering of valuable coproducts to improve the economic feasibility of biofuel production. To accomplish this goal, the desirable traits of the bioenergy crop Sorghum bicolor are harnessed via modern engineering approaches. A robust analysis is provided to highlight the scientific basis, costs, regulatory challenges, and lucrative nature of coproduct development. Sustainable biofuel production could also have far-reaching societal impacts, especially in the context of our rapidly changing global climate. This perspective suggests that the path to profitable biofuel production is attainable and encourages consideration of similar approaches by the biotechnology industry. Graphical Abstract